Two is better than one: verification of the effect of praise from two robots on pre-school children's learning time. (2nd October 2021) - Shiomi, Masahiro; Tamura, Yumiko; Kimoto, Mitsuhiko; Iio, Takamasa; Akahane-Yamada, Reiko; Shimohara, Katsunori
Abstract : This paper reports the effects of praise from two robots on children's learning time, their performance, and their acceptance of the robots. Since praise from a single robot provides positive effects for children as educational support, we hypothesized that praise from two robots will increase such effects because two robots will enhance the social influences. To verify this hypothesis, we developed an English learning system that consisted of an e-learning application, a depth sensor for human-tracking, a tabletop humanoid robot, a doll-type robot, and an operator. We designed the robots to interactively praise children during their learning situations and experimented with a with-in participant design to compare the effects of praise from two robots and just one. 22 children participated in an experiment whose results showed that children learned more when two robots praised them than just one, even with an identical amount of praise. These results suggest the effectiveness and empirical evidence of using two robots for educational support. GRAPHICAL ABSTRACT: UF0001